2014
DOI: 10.1002/jip.1427
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Planning and Violent Behaviours in Serial Homicide: A Cross‐National Comparison Between South Africa and the US

Abstract: Recent literature suggests that different 'styles' of homicide will most appropriately be reflected in the different types of behaviours committed by offenders during the crime. In the last few years, there has been a move to standardise classification systems of single homicides and establish their cross-national generalisability. Literature on serial homicide to date has mostly centred on homicides occurring in the US. However, national differences due to factors such as culture, national identity, political… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…the continued commission of homicides) is contingent upon their ability to choose the best strategy in planning each of their crimes that would enable them to not only complete the present homicide but also successfully evade capture (thus allowing them to commit subsequent crimes). Sorochinski and Salfati (2010) and Sorochinski et al . (2015) showed that each of these may be conceptualised as a distinct cognitive strategy, namely, pre‐offence planning—plans for steps to be taken prior to the crime (e.g.…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…the continued commission of homicides) is contingent upon their ability to choose the best strategy in planning each of their crimes that would enable them to not only complete the present homicide but also successfully evade capture (thus allowing them to commit subsequent crimes). Sorochinski and Salfati (2010) and Sorochinski et al . (2015) showed that each of these may be conceptualised as a distinct cognitive strategy, namely, pre‐offence planning—plans for steps to be taken prior to the crime (e.g.…”
Section: Methodsmentioning
confidence: 92%
“…The offender's goal of killing the victim may be achieved using different strategies, some of which may be more efficient than others. Sorochinski and Salfati (2010) and Sorochinski et al . (2015) showed that two distinct behavioural themes were evident, each of which reflects a different cognitive strategy.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations